Coordination Models and Languages : 17th IFIP WG 6.1 International Conference, COORDINATION 2015, Held as Part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, Grenoble, France, June 2-4, 2015, Proceedings - Holvoet, Tom.; Viroli, Mirko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 17th International Conference on Coordination Models and Languages, COORDINATION 2015, held as part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, in Grenoble, France, in June 2015. The 14 full papers and one short paper presented were carefully reviewed and selected from 36 submissions. They are organized in topical sections on tuple-based coordination, coordinating ensembles, constraints, agent-oriented techniques and shared spaces.
Replica-Based High-Performance Tuple Space Computing -- Investigating Fluid-Flow Semantics of Asynchronous Tuple-Based Process Languages for Collective Adaptive Systems -- Logic Fragments: A Coordination Model Based on Logic Inference -- Comingle: Distributed Logic Programming for Decentralized Mobile Ensembles -- Dynamic Choreographies: Safe Runtime Updates of Distributed Applications -- Type Reconstruction Algorithms for Deadlock-Free and Lock-Free Linear -Calculi -- A Fix point-Based Calculus for Graph-Shaped Computational Fields -- Take Command of Your Constraints! -- A Labelled Semantics for Soft Concurrent Constraint Programming -- Parallelisation and Application of AD3 as a Method for Solving Large Scale Combinatorial Auctions -- Handling Agent Perception in Heterogeneous Distributed Systems: A Policy-Based Approach -- Blending Event-Based and Multi-Agent Systems Around Coordination Abstractions -- Klaim-DB: A Modeling Language for Distributed Database Applications -- Open Transactions on Shared Memory -- VISIRI - Distributed Complex Event Processing System for Handling Large Number of Queries.
Keywords: Software engineering; Logic design; Computer science; Computer software; Software Engineering; Logics and Meanings of Programs; Programming Techniques; Programming Languages, Compilers, Interpreters; Algorithm Analysis and Problem Complexity